Management of Critical Capabilities to Improve Organizational Effectiveness - Piirto, Joona (My University, 2017)
It can be stated that knowing the most powerful factors in predicting improved effectiveness is an asset to any organization. The challenge, which most organizations are keen to resolve, is to identify the factors associated with the improvement of organizational effectiveness and by what means the factors can be influenced. This research focuses on how to improve the effectiveness of a case organization which operates in a specific industry field with high and unique business requirements by ascertaining the factors with most expected impact to the organization effectiveness, and to design a plan to leverage those factors meaningfully. The theoretical framework of the study is constructed to form the interconnection that organizational effectiveness can be improved by managing the critical organizational capabilities. Strategic leadership, sustainable competitive advantage and knowledge management are briefly reviewed to provide a comprehensive view on the concept of organizational capabilities. Building and measuring of an organizational capability is also studied to incorporate the essential elements to the research process and to the development of the lead indicators for organizational effectiveness. The empirical data of this study is collected in two phases. Within the first phase, Analytical Hierarchy Process (AHP) method is utilized with the management team of the organization to determine the critical organizational capabilities. In the second phase, survey questionnaire was designed for the whole organization to examine the attributes of the organizational capabilities through method called Balanced Critical Factor Index (BCFI). The results demonstrated that Leadership, Talent and Learning are critical capabilities for the case organization. Additionally, the study revealed the attributes within the critical capabilities to which subjected improvement efforts are expected to yield the most considerable impact to organizational effectiveness. In respect to the findings, the thesis describes the development actions and indicators which enable the improvement of organization effectiveness through management of critical organizational capabilities.
Keywords: Organizational Effectiveness; Organizational Capabilities; Intangible Assets; Knowledge Management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|